Pre-operative Ultrasonographic Evaluation of Inferior Vena Cava Collapsibility Index as a Predictor for Hypotension after Spinal Anaesthesia - Yadav, Rajiv; Yadav, Ila; Bharti, Srijan; Singh, Sujeet (Nepal Medical College Journal, 2025)
Postspinal anaesthesia hypotension is a common side effect and can lead to significant morbidity and mortality. Inferior venacava collapsibility index (IVC-CI) and diameter of the inferior venacava (IVC) are two widely used parameters for assessing the intravascular volume status. In this study, we evaluated inferior vena cava collapsibility before surgery topredict hypotension after spinal anaesthesia. In this hospital based observational study, 80 patients aged 18-60 years of ASA physical status I and II undergoing surgery below umbilicus under spinal anesthesia. The IVC-CI and IVC diameter were measured using ultrasound pre-operatively. After administering spinal anaesthesia, haemodynamic data were collected till 18 min. Our general objective was to evaluate the predictive value of IVC-CI for detecting post-spinal hypotension and specific objectives were to to measure IVC diameter, calculate IVC-CI, measure MAP, SBP, DBP. We constructed the receiver operator characteristic (ROC) curves for IVCCI and obtained the best cut-off values. The post spinal hypotension occurred in 18 (22.5%) patients. IVC-CI had a sensitivity of 18.0%, a specificity of 76.0% and a positive predictive value of 18.0%, negative predictive value of 76.0% for predicting hypotension following spinal anesthesia at a cut off value of >42.0%. The IVC-CI had poor diagnostic accuracy for prediction of hypotension after spinal anesthesia for surgery below umbilicus.